FROUDE NUMBER VARIANCE WITH RESPECT TO THE HYDRODYNAMIC RESPONSE OF A NON-STATIC VEHICLE ON A LOW-LYING FLOODED ROADWAY - Shah, S.M.H. (International Islamic University Malaysia-IIUM, 2021)
In terms of stability, the response of static cars in floodwaters has been widely investigated. However, the hydrodynamics of a non-static vehicle exposed to such events are less explored. Herein the study ponders the assessment of the hydrodynamic forces experienced by a non-static vehicle attempting to cross a low-lying flooded street. With that regards, a Perodua Viva was modeled (1:10) and tested in the Hydraulics Laboratory under partial submergence and sub-critical flows, fulfilling the similarity laws. Since the Froude number could best analyze the flow conditions, the behavior of the hydrodynamic forces and the Froude number have been the focus of this investigation. From the study of outcomes, an inverse relation of the Froude number with respect to the buoyancy force, along with positive trends relating to drag, frictional, and rolling resistance, were noticed. Â© 2021. IIUM Engineering Journal. All Rights Reserved.